2008
DOI: 10.1128/ec.00070-08
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide Location Analysis of Candida albicans Upc2p, a Regulator of Sterol Metabolism and Azole Drug Resistance

Abstract: Upc2p, a transcription factor of the zinc cluster family, is an important regulator of sterol biosynthesis and azole drug resistance in Candida albicans. To better understand Upc2p function in C. albicans, we used genomewide location profiling to identify the transcriptional targets of Upc2p in vivo. A triple hemagglutinin epitope, introduced at the C terminus of Upc2p, conferred a gain-of-function effect on the fusion protein.Location profiling identified 202 bound promoters (P < 0.05). Overrepresented functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
129
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(136 citation statements)
references
References 63 publications
7
129
0
Order By: Relevance
“…Znaidi et al (84) observed that upregulation of ERG11 during hypoxia is strictly Upc2p dependent. Upc2p also binds the promoters of four genes encoding transcription factors (INO2, ACE2, SUT1, and UPC2 itself).…”
Section: Oxygen Sensing In Candida Albicansmentioning
confidence: 99%
“…Znaidi et al (84) observed that upregulation of ERG11 during hypoxia is strictly Upc2p dependent. Upc2p also binds the promoters of four genes encoding transcription factors (INO2, ACE2, SUT1, and UPC2 itself).…”
Section: Oxygen Sensing In Candida Albicansmentioning
confidence: 99%
“…Recently, it was proposed that drug resistance and the response to oxidative stress are interconnected processes in C. albicans (Znaidi et al, 2009). This connection exists through the activity of several TFs like Cap1p, Tac1p, Mrr1p or Upc2p for which (i) gain-of-function mutations were observed as being related to clinical azole resistance and (ii) genome-wide studies identified several of their target genes as being involved in the general response to oxidative stress Morschhauser et al, 2007;Znaidi et al, 2009;Znaidi et al, 2008). Also, it is interesting to remind that, in S. cerevisiae, YAP1 was initially described as a gene involved in pleiotropic drug resistance (Wu et al, 1993).…”
Section: Yap Proteins and The Response To Oxidative Stressmentioning
confidence: 99%
“…This suggests that Upc2p/Ecm22p orthologs in pathogenic fungi might play important roles in azole resistance. Indeed, C. albicans harbors a single Upc2p/Ecm22p ortholog (CaUpc2p) that has been implicated in azole resistance (Oliver et al 2007;Dunkel et al 2008;Hoot et al 2008;Znaidi et al 2008). If CaUpc2p by analogy with other zinc cluster transcription factors also interacts with cognate ligands, it might be possible to identify high-affinity small-molecule antagonists that lock CaUpc2p in an inactive conformation, and which could serve as cotherapeutics to enhance the efficacy of standard azole therapy.…”
Section: Therapeutic Implications Of the Identification Of Nuclear Rementioning
confidence: 99%